Perceptions about the health condition of people with obesity - Cátia Suely Palmeira; Laíne Maria Monteiro Garrido; Maria de Lourdes Lima; Armênio Costa Guimarães; Ana Marice Teixeira Ladeia (Rev Rene)
Objective: to understand the perceptions of people with obesity on this health condition. Methods: qualitative research conducted in an outpatient clinic for follow-up of people with obesity. 15 people diagnosed with obesity were interviewed. Data were collected by interviews and submitted to thematic content analysis. Results: three categories emerged: Giving meaning to obesity, Affecting everyday life and health and Facing obesity. In the first category, the majority of respondents gave negative meaning to their own obesity; in the second, they perceived it as a condition capable of causing damage to health and labor capacity; and in the third, it was referred as a condition that must be faced and treated. Conclusion: perceptions on obesity reflected, above all, negative feelings, accompanied by some degree of physical, mental and social suffering.